Efficient multiwavelength generation of Brillouin/erbium fiber laser at 1600-nm region - Harun, Sulaiman Wadi; Tamchek, Nizam; Poopalan, Prabakaran; Ahmad, Harith (John Wiley & Sons, 2002)
An efficient Brillouin/erbium fiber laser, which operates in the 1600-nm (L-band) region, is demonstrated for potential applications in future dense-wavelength division multiplexing communication systems. The laser configuration consists of an L-band EDFA (to enable L-band amplification) where two 3-dB couplers take a portion of the generated BEFL signal and re-inject it into the single-mode fiber in order to seed a cascaded BEFL line in the same direction as the first BEFL line. An efficient BEFL can be obtained by recycling backward a 1550-nm-band amplified spontaneous emission as a secondary pump source for the unpumped EDF in the L-band EDFA section. As a result, the lasing threshold is reduced and slope efficiency is improved. A stable and strong laser comb of up to five lines with 10-GHz spacing has been obtained with a Brillouin pump of 4.8 mW and a 980-nm pump of 92 mW.